2006
DOI: 10.1128/aem.72.1.443-448.2006
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Drug Resistance Genes Do Not Convey a Secondary Fitness Advantage to Calf-Adapted Escherichia coli

Abstract: Maintenance of antimicrobial drug resistance in bacteria can be influenced by factors unrelated to direct selection pressure such as close linkage to other selectively advantageous genes and secondary advantage conveyed by antimicrobial resistance genes in the absence of drug selection. Our previous trials at a dairy showed that the maintenance of the antimicrobial resistance genes is not influenced by specific antimicrobial selection and that the most prevalent antimicrobial resistance phenotype of Escherichi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 46 publications
2
34
1
Order By: Relevance
“…This suggests that the intervention had a relatively quick effect on Tet susceptibility but that these changes were not permanent. It is possible that, in the intervention herds, the lack of long-term selective pressure by the use of medicated milk replacers allowed nonsusceptible bacteria surviving in the calf population to compete more successfully against susceptible bacteria for reasons beyond selection pressure (23).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the intervention had a relatively quick effect on Tet susceptibility but that these changes were not permanent. It is possible that, in the intervention herds, the lack of long-term selective pressure by the use of medicated milk replacers allowed nonsusceptible bacteria surviving in the calf population to compete more successfully against susceptible bacteria for reasons beyond selection pressure (23).…”
Section: Discussionmentioning
confidence: 99%
“…The two other most common resistance patterns at the WSU dairy were ASSuT and ASSuTCh (13). None of the tested isolates with these two phenotypes harbored the SSuT element described herein.…”
Section: Relative Diversity Of Ssut Strains In Calvesmentioning
confidence: 99%
“…In a separate study we have shown that the antimicrobial drug resistance genes themselves do not convey obvious selective advantage in the absence of antimicrobial use (13). The aim of the present study was to identify the nucleotide sequence of the DNA of the SSuT antimicrobial resistance genes and to examine the distribution of this genetic element among strains of E. coli and among cattle farms in Washington State.…”
mentioning
confidence: 99%
“…Much of this assumption is based on the expected fitness cost of maintaining the resistance gene(s). Recent studies indicate that the maintenance of resistance might not impose a significant fitness cost [23][24][25][26] or that this cost can be overcome [19][20][21]27 . However, there is also a large background pool of resistance, probably a result of the fact that many resistance genes protect the bacterial cell in such a way that they are likely to be functional against other compounds in the environment.…”
Section: Resultsmentioning
confidence: 99%
“…This assumption has been questioned [19][20][21] , and recent evidence demonstrates that, in the absence of selection pressure due to antibiotic use, resistance levels in bacterial populations are often slow to decline, if at all 5,7,22 . In fact, some organisms with antibiotic-resistant phenotypes and genotypes seem to be fitter than their susceptible counterparts [23][24][25][26] , and compensatory mutations have been observed that allow the resistant organism to retain its fitness level 27 . Many potential selection forces for resistance have been described, including antibiotics, metals and other compounds such as disinfectants.…”
mentioning
confidence: 99%